Tailoring the nanostructure of plasma-deposited CoOX-based thin films for catalytic applications – A step forward in designing nanocatalysts. (October 2022) - Tyczkowski, Jacek; Kapica, Ryszard; Kozanecki, Marcin; Kierzkowska-Pawlak, Hanna; Sielski, Jan; Aoki, Toru; Mimura, Hidenori
Graphical abstract: Highlights: Catalytic cobalt oxide-based thin films with a tailored nanostructure are produced by cold plasma deposition (PECVD). The number and size of Co3 O4 nanocrystallites can be easily controlled by the parameters of the production processes. An original model of nanocrystalline Co3 O4 formation is proposed. Using the Co3 O4 -based thin films, a rational strategy is developed to design nanocatalysts with the desired nanostructure. Abstract: Among the heterogeneous catalysts based on non-noble metals, cobalt oxides, mainly in the Co3 O4 form, are particularly promising materials. Herein, we developed a facile bottom-up approach to synthesize a novel and sophisticated Co3 O4 -based thin-film material with a tailored nanostructure that is crucial for catalytic properties. The films were produced using a low-pressure plasma-enhanced chemical vapor deposition (PECVD) process that was thoroughly analyzed. The as-deposited films, in the amorphous form composed of Co, O, C, and H atoms (called CoOX -based films), were thermally treated (calcined), transforming them into films containing Co3 O4 nanocrystallites. For a fundamental understanding of the transformation process, the calcination was performed in a controlled manner by Raman spectroscopy using the Raman laser as a heat source. An original model to describe the formation of Co3 O4 nanocrystallites was proposed. We have shown that the concentration of Co3 O4 and also the number and size of its nanocrystallites in the films can be rationally tailored to the specific needs by selecting the parameters of the PECVD and calcination processes. Our research provides a practical strategy for the molecular design of nanostructured thin-film catalysts in a controllable way using the PECVD process.